Novel Phthalocyanines as n-Type Semiconductors for Organic Field-Effect Transistors - Zhou, Weiyi (Université d'Ottawa / University of Ottawa, 2021)
Over the past few decades, metal phthalocyanines (MPcs) have been thoroughly investigated as active materials in organic field-effect transistors (OFETs) towards the commercialization of flexible integrated circuits and displays. One of several advantages to MPcs as building blocks for OFETs is the high degree of functionality, from which the choice of metal ion, substituents along with the phthalocyanine framework and axially bound ligands can synergistically tune the physical and self-assembly properties of the material. Recent interest has been directed to the introduction of main-group elements as the central ion of MPcs as an avenue to install both hole and electron transport properties and improve device performance. To prepare materials that are suitable to be employed as the semiconducting active layer in organic field-effect transistors, a family of novel silicon phthalocyanine derivatives was prepared. The synthesis and optoelectronic properties of those new axially disubstituted silicon phthalocyanines are detailed in this work. Axial ligand variation mainly includes alkylsiloxy derivatives. The emphasis of the current thesis, however, is on tailoring the Pc backbone, which includes replacing the four benzene units with pyrazine moieties, extending the degree of conjugation with naphthalene, and introducing substituents on their peripheral positions. Several metal-containing tetra-2,3-pyrazinoporphyrazines are also described, but their applications are limited due to the difficulty of purification. Specifically, Chapter 1 serves as a comprehensive review of main-group phthalocyanines and their use as active materials in organic field-effect transistors. In Chapter 2, silicon tetra-2,3-pyrazinoporphyrazine complexes are explored. The isosteric substitution of CH groups in Pc macrocycle for nitrogen atoms leads to an obvious hypsochromic shift in their main absorption band, and their relatively low energy levels make them promising air-stable n-type organic semiconducting materials for OFETs. The synthesis and characterization of silicon tetra(tert-butyl)-2,3-naphthalocyanine complexes are described in Chapter 3. The extension of π-conjugation leads to obvious bathochromic shifts in the main absorption band. In addition, the introduction of tert-butyl groups on the periphery of the molecule reduces the tendency of the naphthalocyanine molecules to aggregate, thereby increase their solubility. Chapter 4 covers the synthesis and characterization of zinc tetra-2,3-pyrazinoporphyrazine and cobalt tetra-2,3-pyrazinoporphyrazine, whereas more future works are expected. The fifth chapter provides a conclusion to this work, and possible future directions of the research conducted herein.
Keywords: Phthalocyanine; Organic field-effect transistor; n-Type semiconductor